Efeito da dipirona e do ácido acetilsalicílico sobre parâmetros espermáticos e na contração do ducto epidimário da região distal da cauda do epidídimo de rato - Martins, Ana Beatriz Melo (2021)
Dipyrone and acetylsalicylic acid (ASA) are cyclooxygenase inhibitors widely used worldwide for pain relief, fever and inflammation treatment (except dipyrone). However, the effects of dipyrone or AAS on male fertility are still not fully known, mainly considering the epididymis as a putative target for their anti-fertility effects. Therefore, the aim of this study was to evaluate the effects of dipyrone and ASA on sperm parameters, serum testosterone levels and epididymal duct contractions. We used epididymal ducts isolated from epididymis distal cauda from adult male Wistar rats for studying the in vitro effects of dipyrone and ASA (10, 100 and 1000 µM) on contractions induced by phenylephrine, carbacol or KCl. In addition, we treated adult male Wistar rats with free drug vehicle, dipyrone 100 mg/Kg or ASA 100 mg/Kg for 15 days in order to check the serum testosterone levels, sperm parameters (spermatid number, daily sperm production, sperm transit through epididymis and sperm concentration in epididymis) and epididymal duct contractions. We found that in vitro dipyrone 100 and 1000 µM decreased the maximum effect (Emax) for phenylephrine by about 20 and 40%, respectively. Pre-incubation with dipyrone 1000 µM was able to decrease the Emax for carbachol by 30% as well as reduce the potency for carbachol by 3-fold. Similarly, ASA 100 and 1000 µM decreased the Emax for phenylephrine by 20 and 30%, respectively. ASA 1000 µM also reduced the Emax and potency for carbachol by 20% and 2.5-fold, respectively. The in vivo treatment with dipyrone or AAS for 15 days were able to reduce the serum testosterone levels by about 60% for both drugs. We also found a significant reduction in the epididymal sperm number and daily sperm production. On the other hand, the sperm transit time through epididymis and epididymal duct contractions induced by phenylephrine or carbachol were unaltered. In conclusion, the in vivo treatment with dipyrone or ASA reduced the sperm count in epididymis and such effect could be related to a decreased daily sperm production induced by low testosterone levels. Furthermore, we were not able to found any between epididymal motor activity alterations and low epididymal sperm numbers in treated animals.